Photoresponse analysis and pixel shape optimization for CMOS active pixel sensors. - Shcherback, I. (IEEE Transactions on electron devices)
In this work, a semi-analytical model, based on a thorough analysis of experimental data, is developed for photoresponse estimation of a photodiode-based CMOS active pixel sensor (APS). The model covers the substrate diffusion effect together with the influence of the photodiode active-area geometrical shape and size. It describes the pixel response dependence on integration photocarriers and conversion gain and demonstrates that the tradeoff between these two conflicting factors gives an optimum geometry enabling extraction of maximum photoresponse. The parameter dependence on the process and design data and the degree of accuracy for the photoresponse modeling are discussed. Comparison of the derived expression with the measurement results obtained from a 256×256 CMOS APS image sensor fabricated via HP in a standard 0.5-μm CMOS process exhibits excellent agreement. The simplicity and the accuracy of the model make it a suitable candidate for implementation in photoresponse simulation of CMOS photodiode arrays.